2013
DOI: 10.4194/1303-2712-v13_5_09
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study was conducted to determine physico-chemical characteristics and nutrient levels on a monthly basis of the rivers of the Eastern Black Sea region with an average flow rate of about 10 m 3 /sec and above, including Kızılırmak, Yeşilırmak, Melet, Pazarsuyu, Aksu, Harşit, Değirmendere, Solaklı, İyidere, Büyükdere, Fırtına, Çağlayan and Kapistre.The highest annual average values for electrical conductivity (EC), reactive phosphate (o-PO4), ammonium (NH4), nitrite (NO2), sulphate (SO4) and hardness were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…directly passes through the digestive tract, that its optimum temperature requirement is 37°C and that it inhibits the development of many pathogenic microorganisms indicate its probiotic specificity. [20] Witthuhn et al have reported that LAB in kefir grains range from 6.40E+04 cfu/gmL to 8.50E+08 cfu/gmL and yeast levels range from 1.50E+05 to 3.70E+08 cfu/ gmL. Yeast levels in various kefir products have been reported to range from 1E+03 cfu/gmL to 1E+06 cfu/gmL.…”
Section: Discussionmentioning
confidence: 99%
“…directly passes through the digestive tract, that its optimum temperature requirement is 37°C and that it inhibits the development of many pathogenic microorganisms indicate its probiotic specificity. [20] Witthuhn et al have reported that LAB in kefir grains range from 6.40E+04 cfu/gmL to 8.50E+08 cfu/gmL and yeast levels range from 1.50E+05 to 3.70E+08 cfu/ gmL. Yeast levels in various kefir products have been reported to range from 1E+03 cfu/gmL to 1E+06 cfu/gmL.…”
Section: Discussionmentioning
confidence: 99%
“…They are called macro elements and they can enter into aquatic ecosystems in many ways (Çepel, 1996;Bolat & Kara, 2017). Especially nitrogen and phosphorus are necessary for the biochemical cycle but their excessive amounts lead to eutrophication in aquatic ecosystems (Alkan et al, 2013). Also, some elements (Fe, Cl, Cu, Mn, Zn, Mo, B, Ni) are called micro elements.…”
Section: Introductionmentioning
confidence: 99%
“…Although these are necessary to aquatic plants, their high concentrations lead to toxic effects (Çepel, 1996;Bolat & Kara, 2017). High concentration levels of micro and macro elements play an important role in pollution of aquatic ecosystems (Webber, 1981;Alkan et al, 2013). Also, some micro elements can accumulate in sediment, lead to deterioration of water quality, and they reach all organisms by the food web (Seven et al, 2018).…”
Section: Introductionmentioning
confidence: 99%